Partilha de sentidos-e-significados atribuídos à função do tutor presencial - Silva Filho, Leonardo Nogueira da (2015)
The following study has as main goal to investigate the functions of the present tutor in the process of teaching-learning distance education students. In order to guide our study, we propose the following research question: which senses and meanings are shared between present tutors, in relation to their functions, in reflective conversation? This research is rooted in two theoretical bases: (1) the socio-historical and cultural theory, discussed from Vygotsky s writing (1934/2002; 1932/1984), and from some of his renowned readers, Newman and Holzman (2002), Van der Veer and Valsiner (1996), Oliveira (2000), Ivic (2010) and Rego (1994), and (2) the study about distance education, discussed from the study of documents issued by the Ministry of Education and Culture from Federal Government of Brazil and from the thought of Valente (2011; 2003) and Leffa and Freire (2013). Having the Critical Research Collaboration as methodological approach (MAGALHÃES, 2011; 2004; 2003), data were generated and collected in reflective conversation from four meetings between present tutors from a pole in a city that is part of São Paulo. The results point to the most varied senses and meanings referent to the functions of the present tutors. Some senses and meanings are common between the three university contexts and others are specific to a single context. Those differences between functions led us to the observation that the role of the present tutor, different from the role of the professor in present teaching, is not clear, not even for the university contexts, nor for the distance education student, and the tutor himself. We believe that our contribution is due to something that permeated all of our reflective conversation: sharing, an important action among school contexts for us to take knowledge of what are our identities as professionals